Conceptual design of UTM 4-seater helicopter - Ammoo, Mohd. Shariff; Mohd. Nayan, Mohd. Idham; Hussain, Mohd. Nasir (2008)
This paper describes the conceptual design of the first UTM's 4-seater helicopter. The vehicle is in lighthelicopter category and will be powered by piston engine. Parametrics study is used to identify the initial specification in order to initiate the preliminary design of the helicopter. The design process was carried-out in accordance with the FAR Part 27 standard.